Analysis of Megadune Fields in Antarctica - Giacomo Traversa; Davide Fugazza; Massimo Frezzotti (2021 IEEE International Geoscience and Remote Sensing Symposium IGARSS, 2021)
In this research, we present new and updated properties of the megadune fields, which are largely distributed on the Antarctic plateau. We used mainly Landsat 8 OLI imagery in order to characterize the megadune fields using visible and Near Infrared bands. Focusing on two areas where megadunes occur, we provide detailed albedo measurements, both broadband and near-infrared, differentiating their upwind and downwind parts. In addition, we calculated their brightness temperature. Using the wind surface morphology obtained from Landsat 8 OLI images and the REMA DTM, we also calculated the Slope in the Prevailing Wind Direction at about ten meters scale, which provided information about the formation of snow glazed surfaces. Finally, we studied the upwind migration of the megadunes and compared these results with other remote-sensing products and in-situ measurements.